Scenario generation using adaptive sampling: The case of resource scarcity. (May 2016) - Islam, Tushith; Pruyt, Erik
Abstract: Static input-oriented sampling approaches are often used for generating model-based scenarios. However, for models of deeply uncertain and dynamically complex issues, there is no guarantee that such approaches reveal the total behavioral spectrum that could be generated by simulating them. In this paper, we present an adaptive output-oriented sampling approach for exploring the full behavioral spectrum that could be generated by computational models in view of generating interesting, even previously undiscovered, scenarios. In this paper, we use a resource scarcity model to illustrate the approach, show the difference between static sampling and adaptive sampling, and demonstrate the usefulness for scenario discovery of the latter combined with other methods. We show that this approach can be used for revealing the behavioral spectrum of models, identifying regions of the input space that generate particular behaviors, and selecting (sets of) scenarios that are representative in terms of output and input spaces. Highlights: We introduce adaptive sampling to explore the output spectrum of simulation models. We use roughness to characterize the dynamic complexity of transient scenarios. We show that adaptive sampling supports scenario discovery and exemplar selection. Using a resource scarcity model, we identify strengths, weaknesses/improvements.